Inhibition of PI3K-AKT-mTOR Pathway and Modulation of Histone Deacetylase Enzymes Reduce the Growth of Acute Myeloid Leukemia Cells - Sansacar, Merve; Sagir, Helin; Akcok, Emel Basak Gencer; Gencer Akçok, Emel Başak (Humana Press inc, 2023)
One of the most widespread forms of blood cancer is known as acute myeloid leukemia (AML) which has an incidence of 80% with poor prognosis. Although there are different treatment methods for AML in clinic, the heterogeneity and complexity of the disease show that new treatments are needed. The aim of this study is to investigate the anticancer effects of inhibition of PI3K and HDAC enzymes on CMK and MOLM-13 AML cells lines. We demonstrated that the combination of LY294002 with SAHA and Tubastatin A significantly decreased the cell viability of both cell lines. In contrast, the LY294002 and PCI-34051 combination did not show a significant difference compared to the single LY294002 administration. The combination treatment of LY294002 and HDAC inhibitors did not induce apoptosis significantly. However, LY294002 + SAHA and LY294002 + PCI-34051 resulted in G0/G1 and G2/M cell cycle arrest in CMK cells, respectively. On the other hand, compared to control cells, LY294002 + SAHA and LY294002 + PCI-34051 led to G0/G1 phase arrest in MOLM-13. Furthermore, the LY294002 + PCI-34051 combination elevated the expression rate of LC3BII/I, an autophagy marker, in CMK cells by 2.5-fold. Our study revealed that the combinations of PI3K inhibitor and HDAC inhibitors showed a synergistic effect and caused a reduction in cell viability and increased cell cycle arrest on MOLM-13 and CMK cell lines. In addition, the expression of LC3BII was elevated in the CMK cell line. In conclusion, although more mechanistic studies are required, a combinational inhibition of PI3K and HDAC could be a promising approach for AML.
Sagir, Helin/0000-0001-5025-6627; Gencer Akcok, E. Basak/0000-0002-6559-9144; Sansacar, Merve/0000-0002-1731-5215
Keywords: Acute Myeloid Leukemia; PI3K Pathway; Histone Deacetylase Enzymes; Cell Cycle; Combination Therapy